PENGARUH PEMBERIAN PAKAN ALAMI YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP DAN LAJU PERTUMBUHAN LARVA IKAN PERES (Osteochilus sp.) - Syahrinaldi Akhyar; A. A. Muhammadar; Iwan Hasri (Universitas Syiah Kuala, 2016)
This research aims to analyze the effect of feeding different natural against the survival and growth rate (absolute growth of long, heavy growth of absolute and specific growth rate) fish larvae of peres (Osteochilus sp.). This research was conducted at the Unit Implementing Seed Fish Lukup Badak, Department of livestock and Fisheries Pegasing sub-district, Aceh Tengah District in August to September 2015. The fish test was using fish larvae of peres the aged of 3 days with an average length of 0.4 cm and a weight of 0.001 g/tail. Feed natural feed is used it Daphnia sp., Artemia salina, Tubifex sp and Infusoria. Feeding channeled in adlibitum with feeding frequency 4 times a day. Maintenance was carried out on fish aquariums are equipped with aeration. Fish kept for 15 days. Statistical analysis using one-way ANOVA. The experimental design used completely randomized design (CRD) with 4 levels of treatment and 3 replication. The treatments done covers different feeding treatments; A (Daphnia sp.), B (Artemia salina), C (Tubifex sp.), and D (Infusoria). The results of the ANOVA showed that the natural feeding of different influential real against the survival of larval fish growth rate and peres (Osteochilus sp.). Advanced test Duncan also showed that feeding Artemia salina gives the best results in terms of survival (98%), growth of absolute weight (1.02 g), growth of the absolute length (8.81 mm) and specific growth rate (5.68%). These results differ markedly (P 0.05) with the type of Daphnia sp. feeding Tubifex sp, sp and Infusoria.Penelitian ini bertujuan untuk menganalisis pengaruh pemberian pakan alami yang berbeda terhadap kelangsungan hidup dan laju pertumbuhan (pertumbuhan panjang mutlak, pertumbuhan berat mutlak dan laju pertumbuhan spesifik) larva ikan peres (Osteochilus sp.). Penelitian ini dilakukan di Unit Pelaksana Teknis Balai Benih Ikan Lukup Badak Dinas Peternakan dan Perikanan Kecamatan Pegasing, Kabupaten Aceh Tengah pada bulan Agustus sampai dengan September 2015. Ikan uji yang digunakan adalah larva ikan peres berumur 3 hari dengan panjang rata- rata 0,4 cm dan berat 0,001 g/ekor. Pakan yang digunakan adalah pakan alami yaitu, Daphnia sp., Artemia salina, Tubifex sp. dan Infusoria. Pemberian pakan dilalukan secara Adlibitum dengan frekuensi pemberian pakan 4 kali sehari. Pemeliharaan ikan dilaksanakan pada akuarium yang dilengkapi dengan aerasi. Ikan dipelihara selama 15 hari.Analisis statistik menggunakan ANOVA satu arah. Rancangan Percobaan yang digunakan yaitu Rancangan Acak Lengkap dengan 4 taraf perlakuan dan 3 ulangan. Perlakuan yang dilakukan meliputi perlakuan pakan yang berbeda; A (Daphnia sp.), B (Artemia salina), C (Tubifex sp), dan D (Infusoria). Hasil ANOVA menunjukkan bahwa pemberian pakan alami yang berbeda berpengaruh nyata terhadap kelangsungan dan laju pertumbuhan larva ikan peres (Osteochilus sp.). Uji lanjut Duncan juga menunujukan bahwa pemberian pakan Artemia salina memberikan hasil yang terbaik dari segi kelangsungan hidup (98%), pertumbuhan berat mutlak (1,02g), Pertumbuhan panjang mutlak (8,81mm) dan laju pertumbuhan spesifik (5,68%). Hasil ini berbeda nyata (P0,05) dengan jenis pakan Daphnia sp, Tubifex sp dan Infusoria. This research aims to analyze the effect of feeding different natural against the survival and growth rate (absolute growth of long, heavy growth of absolute and specific growth rate) fish larvae of peres (Osteochilus sp.). This research was conducted at the Unit Implementing Seed Fish Lukup Badak, Department of livestock and Fisheries Pegasing sub-district, Aceh Tengah District in August to September 2015. The fish test was using fish larvae of peres the aged of 3 days with an average length of 0.4 cm and a weight of 0.001 g/tail. Feed natural feed is used it Daphnia sp., Artemia salina, Tubifex sp and Infusoria. Feeding channeled in adlibitum with feeding frequency 4 times a day. Maintenance was carried out on fish aquariums are equipped with aeration. Fish kept for 15 days. Statistical analysis using one-way ANOVA. The experimental design used completely randomized design (CRD) with 4 levels of treatment and 3 replication. The treatments done covers different feeding treatments; A (Daphnia sp.), B (Artemia salina), C (Tubifex sp.), and D (Infusoria). The results of the ANOVA showed that the natural feeding of different influential real against the survival of larval fish growth rate and peres (Osteochilus sp.). Advanced test Duncan also showed that feeding Artemia salina gives the best results in terms of survival (98%), growth of absolute weight (1.02 g), growth of the absolute length (8.81 mm) and specific growth rate (5.68%). These results differ markedly (P 0.05) with the type of Daphnia sp. feeding Tubifex sp, sp and Infusoria. w:LsdExce